Nature of property rights and motivation for blue growth: An empirical evidence from the fisheries industry - Alsaleh, Mohd; Abdul Rahim, A. S.; Liu, Ru; Sun, Qingru (John Wiley and Sons Inc, 2023)
If unauthorized resource use is prevented, managing marine resources by allocating property rights may match economic and environmental conservation incentives. However, because of the developing exploitation of marine resources and accompanying pollution, species' living conditions in Europe's waters are changing more quickly than before. By considering the roles of fisheries productivity, intellectual property rights, intellectual capital rights, market size, governance, and economic growth from 1990 to 2022, this paper aims to investigate the dynamic effect of property rights factors on the sustainability of the fisheries industry in 27 European countries. At higher quantiles, the findings showed a significant positive association between governance and fisheries sustainability adopting a new method, the MMQR with fixed effects, the Method of Moments Quantile Regression. In addition, in EU27 nations, the impact of intellectual property rights was favorable and statistically significant from the first to ninth quantiles. The findings show that the EU14 developed nations have more excellent governance and intellectual capital rights than the EU13 developing countries, significantly benefiting fisheries sustainability. In the same way that market size and economic growth condense fisheries sustainability in EU14 developed and EU13 developing countries, it has been discovered that intellectual property rights do the same across all quantiles, supporting the growth hypothesis for fisheries-producing countries. The findings specifically show that the beneficial solid impact of intellectual property rights, market size, and economic development on the sustainability of fisheries is more significant in EU13 developing nations than in EU14 developed countries. These results provide policymakers with helpful information for promoting property rights aspects in EU14 and EU13 nations via effective green technologies in the fisheries sector to meet sustainable development objectives.